Adenoviral Vectors for Gene Therapy of Hereditary Diseases - Anna Muravyeva; Svetlana Smirnikhina (Biology)
Adenoviral vectors (AdVs) are effective vectors for gene therapy due to their broad tropism, high capacity, and high transduction efficiency, which makes them actively used as oncolytic vectors and for creating vector vaccines. However, despite their numerous advantages, AdVs have not yet found their place in gene therapy for hereditary diseases. This review provides an overview of AdVs, their features, and clinical trials using them for gene replacement therapy in monogenic diseases and analyzes the reasons for the failures of these studies. Additionally, current research on the modification of AdVs to reduce immune responses and target delivery is discussed.